Resistensi Ulama Terhadap Konsep Takharuj Dalam Fikih Hanafiyah - Elfia Elfia (Institut Agama Islam Negeri Curup, 2018)
This research is based on the desire to know the cause of rejection (resistance) of ulama to the concept of takharuj which isdeveloped in fikih Hanafiyah. The Hanafiyah scholar follows the way of takharuj (the removal of one or more beneficiaries from the heirs of the beneficiary in return for the benefit of other beneficiaries either by using his own property or from the heritage property. However,there is a weak point in the completion of the law so that scholars outside Hanafiyah refuse and do not practice it. This research is a library research by collecting and reading jurisprudence literature that contains the opinion of the major ulama and Hanafiyah scholars as the primary material. The approach used in this study is a normative approach. There is a resistance (rejection) of scholars to the concept of takharuj submitted by Hanafiyah scholars because takharuj is considered as a legacy sale but the object of trading is not yet or is not clear. This is contrary to the general principle of muamalah maaliyah. Besides, giving inheritance to the heirs before the person died, even though the purpose was to benefit the heirs, violates and conflicts with the prophecy of qath'i, and the principle of ijbari in inheritance.